MASJID APUNG DI DESA SUNGAI KAKAP, KABUPATEN KUBU RAYA - Kholifah, Safira Nur; Irwin, Irwin; Affrilyno, Affrilyno (JMARS: Jurnal Mosaik Arsitektur, 2024)
The mosque is the center of life and activities of Muslims, both for carrying out ukhrawi worship and worldly worship. Along with the times, mosques have become one of the choices in the realm of tourism, namely religious tourism. Religious tourism is a tourism sector that continues to grow in Indonesia, where the majority of the population is Muslim and has a culture of religiosity and culture. The development of mosques in Indonesia and the world shows an increase. Apart from being a place of worship for Muslims, mosques have various functions, both to carry out ukhrawi worship and worldly worship. Sungai Kakap Village is one of the villages that has the potential in the form of an estuary which is one of the national shipping lanes that is still in the development stage (Perda Kubu Raya Number 7 of 2016). The high tolerance between tribes, races, and religions in this region makes acculturation between cultures occur naturally, despite the diverse composition of the population of races and religions. This area is a strategic area in economic and tourism aspects. One of the tourism sectors that has the potential to be developed is religious tourism. The number of availability of worship facilities when compared with the number of adherents of Islam in statistical data, it can be concluded that the distribution of worship facilities in the form of mosques in this area has not been evenly distributed. Therefore, the object of design is "Design of the Floating Mosque Area in Sungai Kakap Village" as a fulfillment of mosque facilities to facilitate worship activities and create tourist attractions that can become a magnet for the region. Contextual Architecture approaches and lighting strategies are used so as to produce a solemn perception in worship and create iconic buildings that can make the area a tourism magnet.